Tree-ring minimum density chronologies of Picea schrenkiana along an elevation gradient in the Tien Shan Mountains, China. Issue 3 (2nd July 2020) - Yu, Shulong; Zhang, Tongwen; Jiang, Shengxia; Zhang, Ruibo; Qin, Li; Shang, Huaming; Zhang, Heli
ABSTRACT: We selected four sampling areas to collect tree-ring samples along an elevation gradient on north-facing slopes in three regions of the Tien Shan Mountains. Samples were collected at sites located at intervals of about 100 m.a.s.l. in each sampling area. For all sampling sites, the mean tree age, mean sensitivity, and standard deviation of the minimum density chronologies were associated with elevation. Within the same region and between different areas, the consistency of the minimum density of tree rings was highest in the high-elevation sites, followed by the low-elevation sites, and lowest in the mid-elevation forest. Marked changes in slope aspect and inclination affected the consistency of the minimum density in the same area. Significant differences were observed in tree-ring density at 2000–2200 m.a.s.l. Several environmental factors influenced the variation in minimum density of tree rings at different elevations; the factors that were significantly affected by high elevation were observed in the western and central regions of the Tien Shan. High-frequency oscillation was the main reason affecting the change in minimum density and significant differences were observed in medium-frequency oscillations before and after the 1980s.